Chondroblastoma‐like osteosarcoma: a clinicopathological and molecular study of a rare osteosarcoma variant. Issue 3 (19th July 2022) - Gaeta, Raffaele; Righi, Alberto; Gambarotti, Marco; Aretini, Paolo; Lessi, Francesca; Mazzanti, Chiara Maria; Mancini, Irene; Pinzani, Pamela; Belgio, Beatrice; Sbaraglia, Marta; Tos, Angelo Paolo Dei; Franchi, Alessandro
Abstract: Objective: Chondroblastoma‐like osteosarcoma (CBLOS) is a rare and poorly understood variant of OS. We examined the clinicopathological, immunohistochemical and molecular features of six CBLOSs to highlight the differences with conventional high‐grade OS (CHGOS) and CB, including CB with aggressive features. Methods: We performed histone 3.3 mutation analysis by gene sequencing and/or immunohistochemistry in all cases, while whole exome sequencing (WES) was performed on two CB‐like osteosarcomas and 11 conventional high‐grade OS. Results: CBLOSs were predominantly localised at acral sites and involved mainly male subjects with a mean age of 29 years. One patient who had metastases at presentation died of disease, while another patient who developed multiple local recurrences and lung metastases was alive with no evidence of disease (ANED) at 294 months. The remaining patients were ANED after a mean interval of 70.8 months. Histologically, all CBLOS presented aggressive features, including nuclear atypia and infiltrative growth. Immunohistochemistry with H3F3 K36M mutant antibody was negative in all CBLOSs, and none of the five tumours tested by gene sequencing had H3F3B mutations. Conversely, all CBs presented the H3F3B K36M variant and were positive for immunostaining with the H3F3 K36M antibody. Two CBLOSs analysed by WES differed in amount and type of mutation from 11 cases of CHGOS. Moreover, CBLOSs showed lower copy number alteration (CNA) score values than CHGOSs. Conclusions: CBLOS presents a different genetic background and a less aggressive clinical behaviour in comparison with CHGOS. Search of the H3F3B K36M mutation is useful in the differential diagnosis with CB. Abstract : Chondroblastoma‐like osteosarcoma is a rare osteosarcoma variant mainly involving acral sites, with a M:F = 5:1, and mean age of 29 years. Presence of nuclear atypia and infiltrative growth allowed the distinction from chondroblastoma. In addition, immunohistochemistry with H3F3 K36M mutant antibody was negative in all cases. Chondroblastoma‐like osteosarcoma shows different genetic background and less aggressive clinical behavior in comparison with central high‐grade osteosarcoma.